2022
DOI: 10.1021/acsanm.2c04778
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Antibacterial Properties of Magnesium Alloys with Copper-Doped Anhydrous Calcium Phosphate Nanoparticles Embedded into the Polycaprolactone Coating for Medical Implants

Abstract: Magnesium alloys are ideal materials in clinical applications for their excellent mechanical properties, while potential cytotoxicity with rapid degradation limits their clinical applications. Moreover, it is also important for implants to avoid inflammation caused by bacterial infections in the early stage of implantation. Therefore, copper-doped anhydrous calcium phosphate nanoparticles were fabricated by the hydrothermal method and dispersed in a dicalcium phosphate dihydrate (DCPD)/Polycaprolactone (PCL) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…For example, bioactive glass nanoparticles can be applied to the surface of metallic implants, fostering a favourable environment for bone growth and integration, and decreasing the likelihood of implant loosening [64]. Similarly, copper nanoparticle coatings have the potential to provide antimicrobial properties to implant surfaces, thus reducing the risk of infection [65].…”
Section: Nanocomposite Coatingsmentioning
confidence: 99%
“…For example, bioactive glass nanoparticles can be applied to the surface of metallic implants, fostering a favourable environment for bone growth and integration, and decreasing the likelihood of implant loosening [64]. Similarly, copper nanoparticle coatings have the potential to provide antimicrobial properties to implant surfaces, thus reducing the risk of infection [65].…”
Section: Nanocomposite Coatingsmentioning
confidence: 99%
“…For a reasonable selection of the core electrospinnable polymeric matrix to develop core-shell biomedical products, the compatibility, solubility, biodegradable, and mechanical properties should be taken into consideration. Polycaprolactone (PCL) is a kind of biodegradable material [47][48][49] and has been widely used as tissue engineering scaffolds [50][51][52]. Elangomannan et al [53] reported a carbon nanofiber/PCL/mineralized hydroxyapatite fibrous scaffold coated on the titanium for corrosion resistance purposes.…”
Section: Introductionmentioning
confidence: 99%